Body groove Delicious dance - Tripoli, Misty; Guertin, Melanie; Black, Benjamin; Ipson, Freddie (United States? publisher not identified, 2017)
"An amazing dance-inspired series that's low impact, low stress yet loads of fun." -- Provided by distributor.
Title from container.
Choreography by Misty Tripoli and Melanie Guertin. Music by Benjamin Black and Freddie Ipson.
Not rated.
DVD, region 1.
113133
Keywords: Exercise; Physical fitness; Aerobic dancing; video recordings (physical artifacts); Videos